Poison prevention practices and medically attended poisoning in young children: multicentre case-control study - Kendrick, Denise; Majsak-Newman, Gosia; Benford, Penny; Coupland, Carol; Timblin, Claire; Hayes, Mike; Goodenough, Trudy; Hawkins, Adrian; Reading, Richard (BMJ Publishing Group Ltd, 2017)
Introduction